THERMOSTRESSED STATE OF THE PLATE, FORMED BY THE WAY OF ONE-SIDED «FREEZING» OF MELT - Ju. S. Postolnik; V. I. Timoshpolskij; I. A. Trusova; P. E. Ratnikov; G. A. Rumjantseva (Литьë и металлургия, 2008)
The mathematical model of calculation of the hardening ingot thermostressed state in elastoplastic raising is offered.